2003
DOI: 10.2490/jjrm1963.40.196
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Medical Rehabilitation for Elderly Stroke Patients during Acute Phase: A Randomized Controlled Trial.

Abstract: The purpose of this study was to clarify the effect of acute phase rehabilitation for improving the impairment and disability of aged stroke patients. [Subjects] Subjects were stroke patients admitted within 1st day from onset to the stroke medical center with stroke unit. Inclusion criteria of subjects were a) cerebral infarction of middle cerebral artery (excluding lacunae stroke) and intra-cerebral hemorrhage (putamen or thalamus), b) first stroke over 70 years old, c) clear or mild impaired consciousness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…For acute stroke hemiplegic patients, it is necessary to acquire ADL at an early stage in addition to getting out of bed and avoiding disuse. Tokumoto et al reported that greater improvement in ADL was observed in acute stroke patients due to the involvement of occupational therapists in the early phase [9,10]. Furthermore, Ezure et al reported that the ADL of post-stroke hemiplegic patients was more strongly related to trunk function than to the functions of the paretic side [11].…”
Section: Discussionmentioning
confidence: 99%
“…For acute stroke hemiplegic patients, it is necessary to acquire ADL at an early stage in addition to getting out of bed and avoiding disuse. Tokumoto et al reported that greater improvement in ADL was observed in acute stroke patients due to the involvement of occupational therapists in the early phase [9,10]. Furthermore, Ezure et al reported that the ADL of post-stroke hemiplegic patients was more strongly related to trunk function than to the functions of the paretic side [11].…”
Section: Discussionmentioning
confidence: 99%